2006
DOI: 10.1038/sj.jid.5700200
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of TGF-β1 Expression May Be Necessary but Is Not Sufficient for Excessive Scarring

Abstract: Transforming growth factor beta 1 (TGF-beta1) upregulation has been implicated in hypertrophic scars and keloids, but it is unclear if it is the cause or an effect of excessive scar formation. In this study, we overexpressed TGF-beta1 in fibroblasts and characterized its role. Normal human dermal fibroblasts were genetically modified to overexpress TGF-beta1 as the wild-type latent molecule or as a mutant constitutively active molecule. TGF-beta1 secretion was measured, as were the effects of TGF-beta1 upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…TGF-ß is a well acknowledged growth factor in keloid formation with extensive scientific focus being placed on this pathway. Interestingly, a recent study by Campaner and coworkers (98) reported that overexpression of TGF-ß1 is an important component in the formation of keloid tissue, but is not as sufficient as an independent factor, providing evidence for the hypothesis that keloid formation is a multifactorial process (38).…”
Section: Genetics and Immunologymentioning
confidence: 99%
“…TGF-ß is a well acknowledged growth factor in keloid formation with extensive scientific focus being placed on this pathway. Interestingly, a recent study by Campaner and coworkers (98) reported that overexpression of TGF-ß1 is an important component in the formation of keloid tissue, but is not as sufficient as an independent factor, providing evidence for the hypothesis that keloid formation is a multifactorial process (38).…”
Section: Genetics and Immunologymentioning
confidence: 99%
“…Also, neuro-endocrine signals (Ferreira et al, 2009) and an angiogenic component have not yet been incorporated in this HTscar model. Also, extensive screening for more parameters, such as increased TGFβ1 (Campaner et al, 2006) or CTGF (Moon et al, 2012), might further improve the model and provide more insight into human HTscar formation. Another limitation is that only therapeutics that can be dissolved in the culture medium have been studied.…”
Section: Referencesmentioning
confidence: 99%
“…42 Fibroblasts overexpressing the TGF-β 1 gene increase α-SMA expression and enhance FPCL contraction, and the TGF-β/ Smad pathway is involved in inducing α-SMA expression. 18,43 α-SMA is characteristically expressed by myofibroblasts in the skin and is considered a marker of differentiation of fibroblasts to myofibroblasts. Myofibroblast differentiation is widely considered a crucial factor contributing to wound and scar contraction.…”
Section: Ilk-pi3k/akt Pathway and Wound Contraction G LI Et Almentioning
confidence: 99%
“…It contributes to wound contraction. 18 Recent studies suggest that ILK is a key intracellular mediator in the 'crosstalk' between an integrin and the TGF-β 1 pathway. ILK overexpression promotes α-SMA expression as well as epithelial-mesenchymal transition (EMT) in renal tubular epithelial cells.…”
mentioning
confidence: 99%